Alternative sources of business development: Mezzanine financing - Sazonov, Sergey Petrovich; Ezangina, Irina Alexandrovna; Makarova, Elena Anatolievna; Gorshkova, Natalia Valerievna; Vaysbeyn, Konstantin Dmitrievich (Univerzita Pardubice, 2016)
The purpose of the study is to conduct a comprehensive analysis of the nature of mezzanine financing, its pros and cons, role in the system of investment activity in the world practice, as well as to assess the degree of adoption of the tool at the national capital market in Russia. The study lists multiple options of realization and tools of mezzanine financing with private placement. The characteristic features of this type of financial product are listed. Belonging to the mezzanine area of bridge financing is proved, as well as a new mortgage refinancing tool – "factory of mortgage-backed securities." The significance of the use of the mezzanine product in the state support programs abroad, as well as in Russia in the field of residential mortgage lending and co-financing of international transactions, was emphasized. The admissibility of various structures of the transaction and therefore its universality were determined as the basic advantage of mezzanine financing. The subjects of mezzanine capital were described, acting both as a lender and investor due to its specifics. The conclusion emphasized the limited possibilities of the development of mezzanine financing practice in Russia, mediated by the passivity of credit institutions, as well as the imperfection of the legislation regulating loan subordination and mortgage loan securitization.
Keywords: option; mezzanine financing; mezzanine loan; bridge financing; mezzanine financing fund; mortgage security; convertible debt note; E52; G11; F21; O16